Implications of the growth of China and India for the other Asian giant : Russia - Ianchovichina, Elena; Ivanic, Maros; Martin, Will (2012)
Continuing rapid growth of China and India can be expected to raise incomes in Russia, but also to put adjustment pressure on Russian firms. The impacts of the rapid growth of China and India on the Russian economy are explored by examining a baseline projection using a global general equilibrium model, and then assessing the implications of higher-than-expected growth in China and India. The authors find that a major source of benefits to Russia is likely to be terms-of-trade improvements associated with higher energy prices - a quite different channel of effect from that for many developing countries that benefit primarily through expanded opportunities to trade directly with these emerging giants. Taking into account the likely improvements in the quality and variety of exports from China and India, the gains to Russia increase substantially. The expansion of the energy sector and the contraction of manufacturing and services are a sign of a Dutch disease effect that will increase the importance of policies to encourage adaptation to the changing world environment.